Two new species and a new record of polydesmoid millipedes from Jiangsu and Zhejiang provinces, eastern China (Diplopoda, Polydesmida) - Liu, Weixin; Huo, Qingbo (Zootaxa, 2020)
The millipede, Niponia nodulosa Verhoeff, 1931 is recorded from Jiangsu and Zhejiang provinces, eastern China, for the first time. Two new species of the genus Epanerchodus Attems, 1901 are described from the Jiangzhe Area: Epanerchodus campus n. sp. and Epanerchodus bishou n. sp..